Neuropsychiatric and Psychosocial Issues of Patients With Hepatitis C Infection: A Selective Literature Review - Modabbernia, Amirhossein (Kowsar, 2013)
CONTEXT: We briefly reviewed the evidence on the association of hepatitis C (HCV) infection with several aspects of mental and psychosocial health. EVIDENCE ACQUISITION: Medline was searched with appropriate keywords. The primary sources were the systematic reviews. If systematic reviews were not available for a subject, then the most relevant and methodologically sound original studies were selected. RESULTS: HCV infection is associated with poorer health-related quality of life, and physical, mental, and social health. A part of impaired health of these patients is related to cirrhosis, intravenous drug use, co morbid psychiatric disorders, stigmatization, poor social support, alcohol abuse, and interferon treatment. However, HCV itself is also associated with poorer health status particularly in the physical and cognitive domains, which might be related to brain alterations induced by the virus. Interferon treatment is an important cause of depression in HCV patients and sometimes is associated with irritability, manic episode, or acute confusional state. Social health of HCV patients is significantly impaired by stigmatization, poor social support, psychiatric comorbidties, and impaired coping. Psychosocial impairment of HCV patients significantly impairs their treatment adherence. A supportive and nonjudgmental multidisciplinary team is required for optimal management of these patients. CONCLUSIONS: Patients with HCV infection had complex neuropsychiatric and psychosocial problems. These problems are challenges for management of HCV infection, affect the patient’s care significantly, and might alter the course of the disease. A multidisciplinary approach, a supportive environment, and a nonjudgmental healthcare team are required for optimal medical and psychosocial management of patients with HCV.